Airway management in Ludwig's angina: A narrative review - Ujwal Kumar Malladi (Oral Oncology Reports)
Background: Ludwig's angina is a life-threatening condition that causes edema and obstruction of airways leading to mortality if not treated adequately. While handling such cases maintenance of airway becomes a challenge. Main text: Keeping this in mind, this literature review was performed by searching various databases like Pubmed, Google Scholar and Embase using key words Ludwig's Angina, Airway Management and Airway Compromise. Conclusion: Proper airway management is imperative for survival of patients presenting with Ludwig's Angina. Conservative or aggressive approach to maintenance of airways depends on the experience of the anesthesiologist and the condition at which the patient presents.